Nilai –Nilai Kemanusiaan Dalam Novel Sang Saudagar Karya Sultan Ali Bumi (Kajian Struktural Genetik) - Andayani, Lies (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Values of Humanity in the novel “Sang Saudagar” (Genetic Structural Research). Thesis. Jakarta: Master Study Program of Indonesian Education, Post Graduate Study of Muhammadiyah University of Prof. Dr. Hamka Jakarta, 2015. This study aims to find the human values contained in the novel “Sang Saudagar”. To achieve these objectives, this study used theory of text interpretation by the method of content analysis. The technique used in this study is a technique based on the theory of genetic. Research disclosure humanitarian values using qualitative research, the formal text of novel “Sang Saudagar” of Sultan Ali Bumi in the form of words, sentences, and discourse. The results showed that the novel “Sang Saudagar” contains many human values that exemplary by the readers. Human values are: 1) policy, 2) perseverance, 3) compassion, 4) justice, 5) self-control, and 6) quality. Medium of developing human values in the story is through the background story, view of life figuress, the character's mind, character dialogue, action figures and events of the story..